Preoperative geriatric nutritional risk index is a useful prognostic indicator in elderly patients with gastric cancer - Hirahara, Noriyuki (Oncotarget, 2020)
Background: The geriatric nutritional risk index (GNRI) was developed to evaluate the prognosis in elderly hospitalized patients at risk of malnutrition and related morbidity and mortality. This study aimed to evaluate the relationship between preoperative GNRI and long-term outcomes in elderly gastric cancer patients. Materials and Methods: We retrospectively reviewed 297 consecutive patients aged ≥ 65 years who underwent laparoscopic gastrectomy with R0 resection and evaluated their overall survival (OS) and cancer-specific survival (CSS). Results: In the univariate analyses, OS was significantly associated with the American Society of Anesthesiologists Physical Status (ASA-PS), tumor size, tumor differentiation, pathological stage, carcinoembryonic antigen (CEA), C-reactive protein, postoperative complications, and GNRI, whereas in the univariate analyses of CSS, ASA-PS, tumor size, tumor differentiation, pathological stage, CEA, postoperative adjuvant chemotherapy, and GNRI were significantly associated with poor prognosis. In the multivariate analysis, ASA-PS, tumor differentiation, pathological stage, and GNRI were significant independent prognostic factors of OS, whereas ASA-PS, pathological stage, and CEA were significant independent prognostic factors of CSS. Conclusions: GNRI is significantly associated with OS and CSS in elderly gastric cancer patients and is an independent predictor of OS. It is a simple, cost-effective, and promising nutritional index for predicting OS in elderly patients.